Religious and Sexual Identities: An Intersectional, Longitudinal Examination of Change in Therapy. (April 2017) - Lefevor, G. Tyler; Janis, Rebecca A.; Park, So Yeon
The current study employs an intersectional framework to understand how well counselors are meeting the needs of lesbian, gay, bisexual, queer, questioning (LGBQQ) and religious clients by examining clients' initial anxiety and depression levels and changes in these symptoms through psychotherapy. Data from 12, 825 participants from the Center for Collegiate Mental Health 2012–2014 data set were analyzed. Results from hierarchical linear modeling indicate lower baseline anxiety and depression among religious clients and faster rates of change of anxiety symptoms among nonreligious clients. LGBQQ clients presented with higher initial anxiety and depression, but there were no differences in rates of change of anxiety and depression between heterosexual and LGBQQ clients. Significant but minimal interaction effects between religious and sexual identities were found, indicating a need for further research. Counselors are encouraged to be mindful of these disparities in therapy.